2020
DOI: 10.3390/s20092472
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis for SWIPT Cooperative DF Communication Systems with Hybrid Receiver and Non-Linear Energy Harvesting Model

Abstract: In this paper, we study the outage and throughput performance for the simultaneous wireless information and power transfer (SWIPT) cooperative decode-and-forward (DF) communication systems. The hybrid receiver that uses both time switching (TS) and power splitting (PS) methods for energy harvesting (EH) and information decoding (ID), and the piece-wise linear EH model that captures the non-linear input-output characteristic of the EH circuit, are considered. We present exact analytical expressions of the outag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Depending on a practical model of distance and path loss such as used in (e.g., [ 10 , 11 , 25 ]), we consider that are location-based clustering model and placed between S and D in one straightness, so the distance between S and is given as . Without loss of generality, the system model parameters are defined in Table 1 unless otherwise stated.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on a practical model of distance and path loss such as used in (e.g., [ 10 , 11 , 25 ]), we consider that are location-based clustering model and placed between S and D in one straightness, so the distance between S and is given as . Without loss of generality, the system model parameters are defined in Table 1 unless otherwise stated.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…We follow location-based clustering model where the relays set are grouped relatively near each other. In the area of relay selection schemes this proposition is widely used (e.g., [ 10 , 11 , 25 ]) which means equal average channel power gains of B-R, S-R, and R-D links.…”
Section: System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Since QoS in SWIPT with CoR is directly affected by time and power fraction, authors in [102] worked on finding optimized values of TS parameter (α) and PS ratio (ρ) to maximize the capacity using Lagrange multipliers. SWIPT with cooperative DF systems and non-linear EH model with hybrid relaying protocol was studied in [103]. OP and throughput performance were studied and it was shown that optimal values of ρ and α as well as determining optimal positioning of relay minimizes OP of systems.…”
Section: Hybrid Protocol (Tsr-psr) Protocolmentioning
confidence: 99%
“…Recently, with the rapid growth of the number of users and data traffic of wireless networks, greater coverage and higher information capacity are required to better meet users’ demands. At the same time, many energy-limited wireless devices including Internet of Things (IoT) [ 1 , 2 , 3 ] devices are expected to be deployed with limited battery capacity, which require being charged frequently.…”
Section: Introductionmentioning
confidence: 99%